(untitled) (American Journal of Islam and Society, 2015)
Istanbul Think-House (IDE), a self-supported independent research center that promotes the free circulation of ideas, analyzed “Islamism in the Post-Arab Spring World” during its October 24-26, 2014, international conference. Istanbul University’s Political Science Faculty Alumni Association and the Association for Human Rights and Solidarity with the Oppressed (MAZLUMDER) hosted the event on their premises. In his opening remarks on Friday morning, conference co-chair and IDE’s general coordinator Halil Ibrahim Yenigun (Istanbul Commerce University) introduced IDE and explained its vision of (1) producing and circulating ideas without depending on big capital and political power centers and (2) concentrating solely on the good of humanity, especially that of the subaltern. IDE is the outgrowth of national conferences on Islamism held during 2012-13, the first event of which had sparked an almost year-long debate in Turkey about the revival of Islamism. The morning panel, “New Islamisms,” dealt with with important theoretical arguments. Gökhan Sümer (University of Essex) began with a central debate on how to reconcile the constitutional system and the Shari‘ah by broaching such questions as to whether democratic constitutions ensuring the basic rights and freedoms could have been passed after the Arab Spring and what is Islam’s normative status in these new constitutions. He said that such ...